STUDY OF THE RELATIONSHIP BETWEEN THE QUALITY OF ACCOUNTING INFORMATION IN FINANCIAL STATEMENTS AND THE QUALITY OF AUDITING: AN ANALYTICAL STUDY OF JOINT STOCK COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Abbas Fadel Chiyad (Scholars Digest Publishing, 2024)
Financial reports produced or issued by all joint stock companies are among the most important means by which to measure the outcome of those companies' ongoing activity and know their financial position within a certain period of time. The concept of accounting information has been addressed in terms of its definition, characteristics and importance in improving users' decisions. The concept of quality has been addressed in the audit process by its importance and objectives, with an indication of the role of the internal auditor and auditor who belongs to the Audit and Audit Profession Board and who is the external auditor of these companies. The researcher used the analytical description using an identification for the purpose of achieving the research objective consisting of (10) Paragraphs for the collection and analysis of preliminary information on the research sample using the statistical programme (SPSS) was distributed to a group of financial managers, internal auditors and management, as well as auditors and external audit offices, in order to achieve research objectives and thereby arrive at conclusions and research recommendations drawn from theoretical and practical aspects.
Keywords: accounting information, quality, financial reports, comptroller, internal auditor, joint stock companies, occupation board.